FEATURES AND PROBLEMS OF MONETARY REGULATION IN RUSSIA - A. Berdyshev (Вестник университета, 2019)
Based on the analysis of the particularities of the monetary policy of the Bank of Russia in the period 2000-2018, an assessment of its effectiveness has been carried out and the main problems in the sphere of monetary regulation have been identified. It has been determined, that the Bank of Russia focuses solely on ensuring price stability, limits the availability of credit for enterprises in the real sector of the economy, which significantly reduces their development potential. It has been shown, that under the conditions of unjustified monetary policy rigidity, the efficiency of the banking system’s function of transforming savings into investments is reduced. Thus, the easing of the monetary policy by the Bank of Russia is considered as a necessary condition for the development of national production.